Improvement and Development of MSME Go Export on Jogja MSME Nglarisi Partner - Dama Dama; Eva Yuniarti Utami; Rohmawan Adi Pratama; Novi Ria Rahmawati; Rosita Mei Damayanti; Diah Pramesti; Wahyu Agung Setyo (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
This service activity focuses on the Jogja MSME Nglarisi Partner in Yogyakarta. The purpose of implementing a community service program is to create an Export Destination Product Development Program. MSME products have an understanding of international markets. They can take advantage of global e-commerce to increase the quantity and quality of production of Nglarisi MSME products and increase product sales. Mitra Nglarisi Jogja has the potential to develop a broader market, one of which is the international market. The programs created are primary training, including export education training, ecommerce management training, and product management training. The output of the community service program is the development of an understanding to open potential and readiness to enter the international market.